PtI2(DACH), the iodido analogue of oxaliplatin as a candidate for colorectal cancer treatment: chemical and biological features. Issue 10 (23rd February 2017) - Cirri, D.; Pillozzi, S.; Gabbiani, C.; Tricomi, J.; Bartoli, G.; Stefanini, M.; Michelucci, E.; Arcangeli, A.; Messori, L.; Marzo, T.
Abstract : PtI2 (DACH) has been prepared and tested. PtI2 (DACH) shows different chemical and biological features than oxaliplatin, manifesting cellular effects nearly comparable to those of parent drug in three cellular lines of CRC. Abstract : Colorectal cancer (CRC) is a global health problem being the fourth most common cause of death due to cancer worldwide. Oxaliplatin plays a key role in current CRC treatment but shows serious drawbacks, such as a high systemic toxicity and the frequent insurgence of Pt resistance. In search of novel and more efficacious Pt-based drugs for CRC treatment, we synthesized and characterised PtI2 (DACH), an oxaliplatin analogue. PtI2 (DACH) was obtained through the replacement of bidentate oxalate with two iodides. PtI2 (DACH) turned out to be more lipophilic than oxaliplatin, a fact that led to an enhancement of its cellular uptake. In contrast to oxaliplatin, PtI2 (DACH) showed a scarce reactivity towards model proteins, while maintaining affinity for a standard DNA oligo. Notably, PtI2 (DACH) induced cytotoxicities roughly comparable to those of oxaliplatin in three representative CRC cell lines. Moreover, it was able to trigger cell apoptosis, to an extent even better than cisplatin and oxaliplatin. Overall, a rather promising picture emerges for this novel Pt drug that merits, in our opinion, a deeper and more extensive preclinical evaluation.